Proposta de gamificação para a promoção da saúde através do exercício da cidadania: exemplo de aplicação no controle do Aedes aegypti - Lima, Rafael Medeiros de (2021)
The present research proposes a Gamification framework development, that helps health and education professionals to use gamification in developed products that’s stimulate the development of health habits towards citizenship exercise. To a non-game professional to develop a gamified product is not a simple task, only to input some game elements do not guarantee the desired engagement of the public target. In many ways this block professionals to gamify his or her own product. With that mindset this text aims to help this professional to gamify his products toward the public health. This framework was created based on others already consolidated frameworks. As case study: Aedes aegypti, was used as validation for health and education professionals. The results show that this framework is viable and its use was possible to 40% of the professionals researched, however it still need to improve